American visions the epic history of art in America - Hughes, Robert 1938-2012 (A Borzoi book, 1997)
The intense relationship between the American people and their surroundings has been the source of a rich artistic tradition. American Visions is a consistently revealing demonstration of the many ways in which artists have expressed this pervasive connection. In nine eloquent chapters, which span the whole range of events, movements, and personalities of more than three centuries, Robert Hughes shows us the myriad associations between the unique society that is America and the art it has produced: O My America, My New Founde Land explores the churches, religious art, and artifacts of the Spanish invaders of the Southwest and the Puritans of New England; the austere esthetic of the Amish, the Quakers, and the Shakers; and the Anglophile culture of Virginia